PEMANTAUAN TEKANAN DARAH PADA KELOMPOK IBU HAMIL DI DESA AWANG BANGKAL BARAT - Rita Kirana; Agus Rachmadi; Isnaniah, Isnaniah (JURNAL PENGABDIAN MANDIRI, 2025)
A blood pressure check is the process of finding out how much blood pressure is in the arteries when the heart pumps blood. The tool used in this check is a tensimeter, either in manual or digital automatic form. This check can be done as part of a routine health evaluation or as an early detection of hypertension (high blood pressure) during pregnancy. The purpose of this community service activity is to be a means of disseminating information about hypertension, which can affect various groups, especially in pregnant women. The target of this activity is a group of pregnant women in Awang Bangkal Barat Village. The methods used in this activity include providing education through leaflets distributed, as well as direct examination of blood pressure on several visitors to obtain data. It is hoped that this community service activity can be a medium for delivering useful information to the community and can be applied in everyday life